FISHERMEN ECONOMIC BALANCING OF SOCIETY’S WELFARE (Critical Study of fisherman in Pati and Rembang) - Arpangi Arpangi; Sukarmi Sukarmi; Denny Suwondo (UNISSULA, 2018)
The marine affairs and fisheries is one that has certain mission. Mission inception fishery ports fish in the area of Pati or Rembang the basically is to welfare goldfish the scope of starch fishermen. In the facts that’s not yet fully realized so that solving the problem. Invite number 16/l964 not in accordance local conditions were pestered feel earn a living land due to feel the provisions of box or restricted becouse autonomous regional. The basis of the law of the Regional Regulations respectivelely but not progressing smoothly fisherman using fixed tribal law due to the county needed local. The field of marine affairs and fisheries is one that has certain mission. Inception mission in fishery ports in Pati or Rembang is basically concerned to welfare goldfish the scope of starch society fishermen. The fact is the implementation is not yet fully realized, so that it can solve the problems. Invite number 16/l964 was not in accordance with local conditions and were pestered feel earn a living land due to feel the provisions of box or restricted because of autonomous regional. The basis of the Regional Regulations is respectivelely but it is not progressing smoothly. The fishermen use fixed tribal law due to local demand.